Mobile Hearing Screening in a Rural Community School in Ghana - Denkyirah, Anthony M.; Offei, Yaw Nyadu; Acheampong, Emmanuel K. (Journal of the American Academy of Special Education Professionals, 2019)
Hearing screening in public schools is not common practice in developing countries like Ghana. Yet, the World Health Organization (WHO) (2012) reported that 90% of children with hearing problems live in developing countries. This study was conducted in a rural community in the Central Region of Ghana to find out (a) hearing problems among students in rural community schools, (b) accessibility to hearing screening facilities in rural communities, and (c) benefits mobile hearing screening services could bring to people in rural communities in Ghana. Two hundred forty students from a public high school that served about 7 neighboring rural communities were randomly selected for otoscopy examination and pure tone hearing screening tests. One hundred sixty-five of the students passed both otoscopy examinations and pure tone hearing screening tests while 75 of the subjects failed both tests. Recommendations made included regular school-based hearing screening for all students, and increased access to mobile hearing screening in rural communities.